FOLLOW THE EVENTS IN THE INDONESIAN LANGUAGE EXPRESSIVE SAID TRANSACTION IN THE TRADITIONAL MARKET TOWN OF BAUBAU - Harziko, Harziko; Said, Ikhwan M.; Darwis, Kamsinah (JURNAL ILMU BUDAYA, 2018)
Expressive speech acts are often used in both environments, schools, offices, hospitals and market. This research aims to describe the function of speech is expressive of sellers and buyers in the event of transaction in the traditional market town of Baubau. This qualitative descriptive nature of the research. Sampling is done in purposif. Linguistic phenomena is examined with a pragmatic approach. Research data in the form of verbal data sourced from the conversation of sellers and buyers in a transaction. The data was collected by using the method of observation through the technique of record and note. The data have been analyzed in qualitative descriptive are classified. The results showed that the functions of the seller's expressive speech consists of functions to thank, praise, and function function complained. Furthermore the functions of speech is expressive of the buyer, i.e. the function to thank, praise, function and the function of complaining.